2012
DOI: 10.1177/1078345811421771
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Scope of Practice Issues for Correctional Facility Nurses in Montana

Abstract: The research aims were to (a) explore how correctional facility nurses in Montana perceived the balance between the autonomy required in their field and their scope of practice rights, and (b) contrast the correctional nursing specialty from the more traditional nurse setting. Twenty percent of Montana correctional nurses surveyed said there are times where they simply have to work beyond their state scope of practice boundaries. Respondents were most likely to report that the greatest differences in nursing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…This is particularly important, as correctional facility nurses, by survey, are less likely to refer their clients to other resources and more likely to act as primary health care providers. 14 Our study demonstrated that correctional facility nurses benefited from the educational workshop as indicated by a significant increase in overall HIV knowledge and decreased need for further HIV education postintervention. Of note, positive attitude toward individuals living with HIV did not increase postintervention.…”
Section: Discussionmentioning
confidence: 82%
“…This is particularly important, as correctional facility nurses, by survey, are less likely to refer their clients to other resources and more likely to act as primary health care providers. 14 Our study demonstrated that correctional facility nurses benefited from the educational workshop as indicated by a significant increase in overall HIV knowledge and decreased need for further HIV education postintervention. Of note, positive attitude toward individuals living with HIV did not increase postintervention.…”
Section: Discussionmentioning
confidence: 82%
“…Security issues can be a significant challenge to care (ANA, 2007; Reimer, 2007; White & Larsson, 2012). Policies exist that prevent nurses from engaging in typical caring behaviors, such as touch.…”
Section: Challenges To Caringmentioning
confidence: 99%
“…Working within a specialty that cares for persons who have done injustices to others or have broken the law in various ways may not be socially acceptable. A negative stigma is commonly associated with the specialty, adding to the frustrations of attracting qualified staff (White & Larsson, 2012). More traditional nursing specialties such as oncology nursing, maternity nursing, or gerontology may be more valued by society as they deliver care to a more “deserving” population.…”
Section: Challenges To Caringmentioning
confidence: 99%
“…Nurses are the primary health care providers in correctional institutions, thus correctional health care is a nurse‐driven system . The nursing role is executed within the context of correctional health care policies, professional standards, and correctional institution policies .…”
Section: Introductionmentioning
confidence: 99%
“…One area that correctional nursing leaders must consider for each team member is assessment skills. Strong assessment skills are required in correctional nursing practice for several reasons: to identify the validity of offender concerns; emergency situations require rapid assessment skills, and nursing assessments may be the initial point of offender contact to determine whether additional health care services are required …”
Section: Introductionmentioning
confidence: 99%